Factors Associated with the Choice of Radiation Therapy Treatment Facility in Head and Neck Cancer - Sullivan, Christopher Blake (Laryngoscope, 2020)
OBJECTIVE: To analyze the clinicodemographic characteristics and treatment outcomes of patients receiving post-operative radiation therapy (PORT) at a different treatment facility rather than the initial surgical facility for head and neck cancer. METHODS: Retrospective cohort analysis utilizing the National Cancer Data Base, 2004 – 2015, of patients with a diagnosis of oral cavity/oropharyngeal, hypopharyngeal, and laryngeal squamous cell carcinoma (SCC). Multivariate analysis was completed with multivariate regression and Cox proportional hazard model, and survival outcomes were examined using Kaplan-Meier analysis. RESULTS: A total of 15,181 patients who had surgery for a head and neck cancer at an academic/research center were included in the study population. Of the study population, 4,890 (32.2%) patients completed PORT at a different treatment facility. Treatment at a different facility was more common among patients who were ≥65 years old, white, Medicare recipients, and those with a greater distance between residence and surgical treatment facility, and with lower income within area of residence (each p<0.05). Overall survival was worse in patients completing PORT at a different treatment facility versus at the institution where surgery was completed (61.9% vs. 66.4%; p=0.002). CONCLUSIONS: PORT at a different facility was more common in older individuals, Medicare recipients, those with greater distance to travel, and lower income individuals. Completing PORT outside the hospital where surgery was performed was associated with inferior survival outcomes among head and neck cancer patients.